MopA, the Mn Oxidizing Protein From Erythrobacter sp. SD-21, Requires Heme and NAD+ for Mn(II) Oxidation - Medina, Michael; Rizo, Antonia; Dinh, David; Chau, Briana; Omidvar, Moussa; Juarez, Andrew; Ngo, Julia; Johnson, Hope A. (Frontiers in Microbiology, 2018)
Bacterial manganese (Mn) oxidation is catalyzed by a diverse group of microbes and can affect the fate of other elements in the environment. Yet, we understand little about the enzymes that catalyze this reaction. The Mn oxidizing protein MopA, from Erythrobacter sp. strain SD-21, is a heme peroxidase capable of Mn(II) oxidation. Unlike Mn oxidizing multicopper oxidase enzymes, an understanding of MopA is very limited. Sequence analysis indicates that MopA contains an N-terminal heme peroxidase domain and a C- terminal calcium binding domain. Heterologous expression and nickel affinity chromatography (NAC) purification of the N-terminal peroxidase domain (MopA-hp) from Erythrobacter sp. strain SD-21 led to partial purification. MopA-hp is a heme binding protein that requires heme, NAD+, and calcium (Ca2+) for activity. Mn oxidation is also stimulated by the presence of pyrroloquinoline quinone (PQQ). MopA-hp has a KM for Mn(II) of 154 ± 46 μM and kcat= 1.6 min-1. Although oxygen requiring MopA-hp is homologous to peroxidases based on sequence, addition of hydrogen peroxide and hydrogen peroxide scavengers had little effect on Mn oxidation, suggesting this is not the oxidizing agent. These studies provide insight into the mechanism by which MopA oxidizes Mn.